Peran GLAM dalam pendidikan tinggi untuk pelestarian budaya - Atin Istiarni; Jamzanah Wahyu Widayati (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction: This research aims to explore the factors influencing the implementation of GLAM in academic libraries considering technological, organizational and environmental factors. Method: We used a quantitative approach with Structural Equation Modelling. 91 university librarians in Indonesia responded to the distributed questionnaires. Data analysis: The data was analysed using Exploratory Factor Analysis. Results: The most influential factor is technology at 31.31%, obtained from observations to 14 variables. The second influencing factor is organization with a calculation result of 27.10% obtained from the 10 observed variables. The third influencing factor is environment, with a calculation result of 17.3% based on 3 observed variables. The innovation diffusion in the implementation of GLAM in university libraries as an effort to preserve culture however is not yet ready from a technological and organizational perspective. It is noted that environment is the factor with the least influence. Conclusion: This research uses three factors, namely technology, organization and environment as a theoretical basis for answering problems. Based on the research results, technology is the most influential dominant factor in implementing the GLAM in university libraries. Organization is the second influencing factor, while environment is the third factor.